Mutua disponibilità, prezzi e rimborsabilità di farmaci autorizzati con procedura centralizzata europea - Cipollina, Laura; Folino-Gallo, Pietro; Grande, Daniela; Felisi, Maria Grazia; Ravera, Simona; Ceci, Adriana (Farmeconomia. Health economics and therapeutic pathways, 2002)
The european pharmaceutical market doesn’t seem to be a common integrated european market as far as prices and reimbursements within different countries are concerned. Moreover, to better define such differences, little information is available because of the lack of homogeneous and updated european databases. The aim of this study is to assess mutual availability, prices and reimbursements of innovative drugs authorised by EMEA under European Centralised Procedure between 1995-2000 and marketed in five european countries (Italy, Spain, United Kingdom, France and Denmark). Our results demonstrate that the adoption of different drug-price definition models, within different Member States, is the main cause of the heterogeneity. Currently, in countries adopting a controlled drug-price system, prices are lower than prices set in countries that adopt an uncontrolled drug-price system. In this regard, Italy ranks in a middle position as products marketed in Italy generally have prices lower than in the United Kingdom and Denmark, and higher than in France and Spain. Product availability and level of drug breakthrough in the national markets seem to greatly affect the variations we noted among prices and reimbursements in different countries. Differences we observed emphasize the need of finding a common methodology at european level, in order to define the proven “therapeutic benefit” and the “therapeutic advantage” of innovative drugs, allowing a “right price” and reimbursement to the entitled.